Principles and Therapeutics of Yajna - Sivan P. Priya; Padma Rao; Vivek Padmanabhan; Nallan C. S. K. Chaitanya (Journal of Pharmacy and Bioallied Sciences)
Health is defined as a state of complete physical, mental, and social wellbeing, not merely the absence of diseases or infirmity. Yajna means selfless sacrifices performed along with sacred sounds, the mantras. The procedure includes offering selected herbal and sacred materials to the fire to obtain an array of benefits such as air purification and release of therapeutic compounds (antibacterial, antiviral, antifungal, antidepression, and anticonvulsant) in the form of aerosol that enriches the atmosphere and soil. Microbial intrusions into the human system such as severe acute respiratory syndrome coronavirus 2 have proved their ability to hack the elements such as air, water, and earth to coerce humans’ physical and mental status. Panic during COVID (coronavirus disease) pandemic did not decline despite advanced therapeutic approaches. Vaccinating the human and animals of the entire globe within a specific time may not be a practically viable approach; adopting an alternative strategy that holistically represses the viral outbreak at various levels will support the medical and government authorities. Pandemic-combatted ancestors developed traditional remedies with secret medicinal portions prescribed to perform as rituals. One of those rituals is Yajna. Yajna procedure controls microbial load at both the environmental and zoonotic levels. The purpose of this literature review is to examine the advantages of scientifically establishing a correlation between Yajna and its potential contribution to prevent pandemics like COVID. An online search explored the phytotherapeutics of Yajna and correlated with the noninvasive drug delivery.